Pengembangan Biskuit “Prozi” Tinggi Protein dan Kaya Zat Besi untuk Ibu Hamil sebagai Upaya Pencegahan Stunting: Prozi Biscuit Development - Dinda Yulia Nabilla; Dr. Arif Sabta Aji; Afifah Nufaisah; Wulana Saputri; Veriani Aprilia; Herwinda Kusuma Rahayu; Ryan Salfarino (Amerta Nutrition, 2022)
Background: In the era of new normal during covid-19 pandemic, malnutrition such as protein-energy malnutrition and anemia in pregnant women are common in Indonesia. Increasing energy, protein, and iron intake need to take into account with providing nutritious complementary foods to optimize foetal development during pregnancy. Objectives: This study aimed to develop complementary food product known as Prozi biscuit by using local foods such as mackerel, soybeans, and moringa leaves so that can increase the level of protein and iron intake in biscuits. Also, support the stunting prevention program. Methods: Experimental research was carried out using a single factor and customized random sampling such as T1 (20%;80%), T2 (50%:50%), T3 (80%:20%) and one control formulation which contains 100% wheat flour or T0 (100%:0%). Comparison of ingredients was made using a mixture of flour (10% Moringa leaves, 20% soybean flour, 20% mackerel flour and 50% sweet potato flour) and wheat flour. Data analysis used the One Way ANOVA test to see differences in the content of macronutrients and iron. Results: The higher the proportion of mixed flour added to the formulation will increase the water, ash, protein and fat content and reduce the carbohydrate content of the biscuit. Partial substitution of wheat flour had a significant effect in protein and iron content of the “Prozi” biscuit (6-11% and 1.56-2.73 mg/100 g) (P<0.05). Conclusions: The addition of this mixed flour has a positive effect on increasing protein and iron levels in biscuits. The development of "Prozi" biscuits can be used as PMT biscuits for pregnant women to provide additional protein and iron intake to prevent anemia during pregnancy and prevent stunting.